2021
DOI: 10.1017/s1368980021004821
|View full text |Cite
|
Sign up to set email alerts
|

Basis for changes in the disease burden estimates related to vitamin A and zinc deficiencies in the 2017 and 2019 Global Burden of Disease Studies

Abstract: Background: The Global Burden of Disease (GBD) Study provides estimates of death and disability from 87 risk factors, including some micronutrient deficiencies. Objectives: To review methodological changes that led to large differences in the disease burden estimates for vitamin A and zinc deficiencies between the GBD 2017 and 2019 Studies. Methods: GBD publications were reviewed; additional information was provided by GBD researchers. Results: Vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…14 Bayesian meta-regression software, MR-BRT (Institute for Health Metrics and Evaluation), was used to adjust for known biases for study-level differences including studies that were purely from administrative databases such as HCUP, studies reporting first-ever and recurrent strokes together, studies that reported aggregated stroke subtypes only, and studies that excluded prehospital stroke death in measurement methods and case definitions. 8,15,16 Epidemiologic state-transition disease modeling software, DisMod-MR (Institute for Health Metrics and Evaluation), was used to estimate estimates of incidence and prevalence of stroke. Mortality for stroke and stroke subtypes was estimated using vital registration data coded to the ICD system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Bayesian meta-regression software, MR-BRT (Institute for Health Metrics and Evaluation), was used to adjust for known biases for study-level differences including studies that were purely from administrative databases such as HCUP, studies reporting first-ever and recurrent strokes together, studies that reported aggregated stroke subtypes only, and studies that excluded prehospital stroke death in measurement methods and case definitions. 8,15,16 Epidemiologic state-transition disease modeling software, DisMod-MR (Institute for Health Metrics and Evaluation), was used to estimate estimates of incidence and prevalence of stroke. Mortality for stroke and stroke subtypes was estimated using vital registration data coded to the ICD system.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of stroke incidence and prevalence were produced by using a broad range of population-representative data sources, including scientific reports of cohorts and registries, population surveys, microdata from registry and cohort studies, and health system administrative data like the Healthcare Cost and Utilization Project (HCUP) . Bayesian meta-regression software, MR-BRT (Institute for Health Metrics and Evaluation), was used to adjust for known biases for study-level differences including studies that were purely from administrative databases such as HCUP, studies reporting first-ever and recurrent strokes together, studies that reported aggregated stroke subtypes only, and studies that excluded prehospital stroke death in measurement methods and case definitions . Epidemiologic state-transition disease modeling software, DisMod-MR (Institute for Health Metrics and Evaluation), was used to estimate estimates of incidence and prevalence of stroke.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in the modelling of VAS in GBD 2019 might have further reduced the impact of VAS. GBD 2019 used a new meta-analysis method for micronutrient modelling that was not applied in GBD 2017 [ 37 ]. The results of the new modelling approach reduced the effect of VAD on measles and diarrheal diseases by an order of magnitude [ 1 , 38 ].…”
Section: Discussionmentioning
confidence: 99%